Estudos sobre o subdesenvolvimento capitalista: as teorias de Paul A. Baran, Andre G. Frank e Ruy M. Marini - Cano, Ricardo Tedeschi [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The underdevelopment is a high relevance subject in researches and studies for the general social sciences. In this monographic paper, the marxist analysis perspective of the phenomenon approached is considerate of great importance to make a deep overlook, historical and structural, about the origins and solutions possibilities for the issues caused by it over several countries. Has been done here a theoretical analysis of three studious marxist authors of the subject: Paul A. Baran, Andre G. Frank and Ruy M. Marini. How they thought underdevelopment? Which were their scientific contributions to this theme? The main goal of this paper is to do a comparative analysis of these authors, synthesize their considerations about the underdevelopment issues and organized a theoretical and conceptual framework for a better understanding of the matters in capitalist development/underdevelopment relationship. To accomplish that, we elected four variables that supports this comparative exercises, they are: the origins, the causes, the consequences and the way-out of the underdevelopment conditions. This monographic work was made through studies of some principals books and articles of the cited authors as well as the reading of others authors that commented their theories and concepts. The considerations about the underdevelopment vitality under a world capitalist logical, rescues the debate on the transformation of this entire society project for another, been this movement the only way possible to reverse the path of the world people’s history and the major part of humankind that still lives into the “necessity kingdom”

O subdesenvolvimento é um objeto de alta relevância na realização de pesquisas, releituras e estudos para as ciências sociais em geral. Considera-se neste trabalho que a perspectiva marxista de interpretação sobre o fenômeno em questão é de vital importância para se realizar uma análise profunda, histórica e estrutural, sobre as origens e as possíveis soluções dos problemas causados pelo mesmo em inúmeros países. Foi feita uma análise teórica de três autores marxistas estudiosos do tema: Paul A. Baran, André G. Frank e Ruy M. Marini. Como eles pensaram o subdesenvolvimento? Quais foram suas contribuições científicas para o tema? O objetivo deste trabalho é através de uma análise comparativa entre os autores, sintetizar suas considerações sobre a problemática do subdesenvolvimento e organizar um arcabouço teórico e conceitual acerca das questões do desenvolvimento/subdesenvolvimento capitalista e suas relações dinâmicas. Para isso, elegemos quatro variáveis que sustentam este exercício comparativo, sendo elas: a origem, as causas, as conseqüências e as vias de superação do subdesenvolvimento. Este trabalho monográfico foi realizado a partir do estudo de algumas das principais obras dos autores citados bem como da leitura de outros autores que comentaram sobre estas teorias e conceitos. As considerações dos autores, sobre a vitalidade do subdesenvolvimento dentro da lógica capitalista mundial, resgatam o debate sobre a transformação deste projeto de sociedade por outra, já que somente assim seria possível reverter o rumo da história dos povos do mundo e de grande parte da humanidade que ainda se encontra submersa no “reino da necessidade”
Keywords: Baran, Paul A., 1910-1964; Frank, Andre Gunder, 1929-; Marini, Ruy Mauro; Economia; Capitalismo; Desenvolvimento econômico